Physical Activity Correlates to Body Mass Index among Medical Students - Vikawati, Nura Eky; Sarosa, Hadi; Makarim, Fadli Rizal; Fasitasari, Minidian (Jurnal Kedokteran Brawijaya, 2020)
Physical activity (PA) has a positive effect on preventing risk on cardiovascular and metabolic syndrome, including obesity. Learning behavior that tends to be sedentary causes medical students to tend to be physically inactive. This present study aimed to associate the physical activity (PA) level with blood pressure, body mass index, and non-fasting blood glucose level (NFBG) among medical students. This cross-sectional study was conducted from February to March in 2019 on the first-year medical students at Sultan Agung Islamic University (UNISSULA). A total of 167 medical students (64.7% female and 35.3% male) were enrolled in this study. The international physical activity questionnaire (IPAQ)-short form was used to measure the PA level. The activity level was classified into low, moderate, and high. Blood pressure and glucose level were measured using a digital sphygmomanometer and NFBG dipstick. The association between PA level and Body Mass Index (BMI), Blood Pressure (BP), and NFBG level were analyzed using Spearman's correlation test. Chi square test was done to analyse the difference of PA level between male and female groups. The majority of the respondents had a low PA level (64.7%). A positive association was shown between PA level and BMI (p<0.05, r=0.192). Female medical students tend to be physically inactive than males (OR 2.004, 95% CI (1.038-3.8690)). Female students need to be encouraged to do more physical activity. The university's policies that promote physical outdoor activity need to be suggested.Â Â